Assessment of the Genetic Connectivity Between Farmed Populations on a Typical Kelp Farm and Adjacent Spontaneous Populations of Saccharina japonica (Phaeophyceae, Laminariales) in China - Shan, Tifeng; Li, Qianxi; Wang, Xuemei; Su, Li; Pang, Shaojun (Frontiers in Marine Science, 2019)
The commercially important brown alga Saccharina japonica in China has been believed to be accidentally introduced from Japan in 1920s. Meanwhile, spontaneous populations in the wild are assumed to be derived from the locally farmed populations. Spontaneous populations are often observed in the subtidal zones and on the cultivation infrastructure near farmed populations in the north of China. However, the genetic connectivity between these sympatric spontaneous and farmed populations remains unclear. Here, three commonly farmed cultivars (farmed populations) and three spontaneous populations (two from subtidal zones and one from cultivation rafts) were sampled from a typical kelp farm in Dalian, China, and analyzed with ten polymorphic microsatellite markers. Genetic diversity of farmed populations was found to be higher than that of the subtidal spontaneous populations. Neighbor joining cluster analysis based on genetic distance, Bayesian model-based structure analysis, and discriminant analysis of principal components revealed significant genetic divergence between the farmed populations and the subtidal spontaneous ones. Gene flow out of farmed populations to the subtidal spontaneous populations was revealed to be very limited, but gene flow in the contrary direction was more prominent. The spontaneous sporophytes on the structural rafts contained pedigree from both farmed and subtidal spontaneous populations. Results of this study may help us to understand reciprocal impacts between sympatric spontaneous and farmed populations of S. japonica